Chiral Aryl Iodide-Catalyzed Enantioselective α-Oxidation of Ketones - Rodríguez, Arantxa; Moran, Wesley J. (Synthesis, 2012)
Several chiral aryl iodides were synthesized and assessed as catalysts in the enantioselective α-oxytosylation of propiophenone and the oxidative cyclization of 5-oxo-5-phenylpentanoic acid to 5-benzoyldihydrofuran-2(3H)-one. The highest enantioselectivities obtained were 18 and 51% ee, respectively. The latter is the highest selectivity recorded to date for this reaction.
Keywords: hypervalent iodine; enantioselectivity; oxidation; asymmetric catalysis; organocatalysis